Analysis Cost Implementation Using Erection Method in Bridge Construction Malo District – Bojonegoro - David Himawan Susetya; Esti Wulandari; Andi Patriadi (Publica Scientific Solution, 2026)
The construction of the Malo Bridge in Bojonegoro Regency encountered significant challenges during the superstructure erection phase, primarily due to limited site accessibility and the use of a less suitable erection method. This study aims to evaluate the comparative efficiency of two primary erection techniques: the use of a 250-ton crawler crane operated from land and a combined method involving a 100-ton crawler crane supported by modular pontoons operating from the water. A case study approach with a quantitative methodology was applied, focusing on three main parameters: erection duration, construction cost, and risk management. The analysis indicates that the land-based 250-ton crawler crane method required a shorter erection period of 181 days, compared to 203 days for the modular pontoon method, resulting in a time-efficiency gain of 10.84%. Furthermore, the 250-ton crawler crane method demonstrated greater cost-effectiveness and a lower level of operational risk. These findings highlight that selecting an erection method that aligns with the site’s geographical and logistical conditions is crucial for optimizing construction performance. Appropriate method selection can lead to significant improvements in both time and cost efficiency, especially in complex or constrained environments.